Indonesia’s Interpretation of the Convention on the Rights of Child - Fatimatuzzahra, Amelia (Universitas Islam Lamongan, 2023)
AbstractThere are lots of children violence such as victims of sexual violence, victims of physical violence, and psychological disorders. Besides it can damage the growth and development of children both physically and psychologically, and the loss of their rights can lead them to acts that are against the law. In Indonesia, violations of children's rights occurred in all regions creating very alarming situations and conditions. That is why Indonesia ratified the Convention on the Rights of Child on August 25, 1990. This research used qualitative research methods with a descriptive approach. The data analysis method used by the researcher is a documentation study method where the data used are primary and secondary data. The researchers would like to analyze the legal and political interpretation of Indonesia to the Convention on the Rights of Child. The result of this research showed that Indonesia interprets the international agreement as a law that needs to be obeyed in the form of â€˜Presidential Decree Number 36 of 1990â€™ which is felt to be effective in Indonesia rather than the form of enactment. It is evidenced by the existence of various state policies and programs in fulfilling the obligations contained in this convention.Â